An Economic Valuation of Sago Forest Harvesting Regimes - Husaini, Sulaiman (2005)
The perception that peat swamp land is a marginal land and sago is a marginal crop is an understatement. It is an understatement that omits the environmental costs and benefits associated with sago peat swamp forest management. Sago peat swamp forest serves important ecological and environmental functions and provides perpetual benefits, if managed in a sustainable manner. One of the measures for sustainability is the valuation of the resource. This study uses the disciplines of economics in order to generate the set of values. Hence the total economic valuation (TEV) approach is adopted. In order to demonstrate the TEV, the components of sago peat swamp forest to be estimated and quantified are the stumpage value, fish, domestic water, carbon sequestration and wildlife. The methods adopted in valuation of these benefits are market price, damage cost avoided and contingent valuation. The objective of the study is to estimate the TEV of sago harvesting regimes that are most efficient both financially and environmentally. The samples are the heads of the households from the villages that surround the study site. This is to ensure the samples are familiar with the study site. iii The analysis is conducted in three parts. The first part is the willingness-to-pay (WTP) for the benefits provided by the Mukah Sago peat swamp forest. The analysis reveals that the determination of WTP is the income earned from the benefits. The second part is the quantification of each component of TEV used in the study. The analysis shows that the economic value is higher under sustainable option when compared with unsustainable option. The final part is the financial analysis. The financial and economic internal rates of return are calculated. The financial internal rate of return highlights only the income derived from the sago logs, the tangible asset. However, the economic rate of return aggregates all the values of the other benefits, both tangible and intangible into the income calculation. The results are significant at both local and state levels. At the local level, the sago peat swamp forest plays an important role in income contribution to the farmers. However, their attitudes towards the conservation and maintenance of the sago peat swamp forest have to change towards sustainability for perpetual benefits. At the state level, sustainability needs proactive management to make the sago peat swamp forest more productive by implementing environmentally friendly projects that generate income for the benefit of the stakeholders.